A must know compendium of genital chlamydia for health care providers - Ponnupillai, Anitha; Madhavan, Priya; Patil, Sapna S.; Earnest, Benjamin S. P. (International Journal Of Community Medicine And Public Health, 2024)
Chlamydia comprises the largest proportion of all sexually transmitted infections (STIs) worldwide. It is caused by Chlamydia trachomatis, an obligate intracellular bacterium and exists in two stages; an extracellular elementary body which is an infectious state and an intracellular reticulate body, a dormant state. The elementary body increases the risk of transfer of chlamydial infection during oral, genital or anal sex. On the other hand, the vegetative state of the reticulate body promotes the chance of latent and recurrent infection. In 2020, WHO estimated 129 million new chlamydia infections. Most of the chlamydial infections are asymptomatic (85-90%) which promotes transfer between partners. If untreated, it can lead to an ascending infection which greatly impacts sexual and reproductive health. In addition, it can infect the baby around childbirth and may result in stillbirth or neonatal death. The immuno-pathogenesis of the chlamydial infection is predominantly evoked by major outer membrane protein (MOMP), a dominant chlamydial antigen on the cell wall; along with the chlamydial antigen, heat shock protein 60 (HSP60) triggers host immune responses. The innate and adaptive immune responses result in extensive fibrosis and permanent damage to the fallopian tube resulting in tubal factor infertility and ectopic tubal pregnancy. The improved strategies in screening, diagnosis, treatment and follow up of Chlamydial infection can have noticeable effects on prevention of incidence, retarding the progression and avoiding recurrence of infection leading to a reduction in the global burden of STIs and the consequent adverse neonatal outcome.